2016
DOI: 10.1534/g3.116.035345
|View full text |Cite
|
Sign up to set email alerts
|

An RNAi Screen To Identify Protein Phosphatases That Function Within theDrosophilaCircadian Clock

Abstract: Circadian clocks in eukaryotes keep time via cell-autonomous transcriptional feedback loops. A well-characterized example of such a transcriptional feedback loop is in Drosophila, where CLOCK-CYCLE (CLK-CYC) complexes activate transcription of period (per) and timeless (tim) genes, rising levels of PER-TIM complexes feed-back to repress CLK-CYC activity, and degradation of PER and TIM permits the next cycle of CLK-CYC transcription. The timing of CLK-CYC activation and PER-TIM repression is regulated posttrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
11
1
Order By: Relevance
“…DBT is a component of PER-TIM repression complexes that is found in CLK-GFP complexes coincident with PER (Supplementary Data S1 ). PPD3 function in the clock was tested previously, but RNAi knockdown of Ppd3 did not alter circadian behavior 45 . The remaining GFP-CLK interactors, Prl-1 , Nipped-A and Ubc6 , were characterized in more detail.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…DBT is a component of PER-TIM repression complexes that is found in CLK-GFP complexes coincident with PER (Supplementary Data S1 ). PPD3 function in the clock was tested previously, but RNAi knockdown of Ppd3 did not alter circadian behavior 45 . The remaining GFP-CLK interactors, Prl-1 , Nipped-A and Ubc6 , were characterized in more detail.…”
Section: Resultsmentioning
confidence: 98%
“…Many other proteins are enriched in GFP-CLK complexes (Supplementary Data S1 ), and a small subset of these proteins associate with GFP-CLK at specific phases of the diurnal cycle. Of these proteins, DBT plays a prominent role in PER phosphorylation and degradation 33 , 64 , 65 and PPD3 has no detectable impact on clock function 45 . RNAi knock down of Prl-1 lengthened circadian period and decreased rhythm strength, while knocking down Nipped-A lengthened circadian period (Table 1 ), consistent with previous work 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The RNAi technique has evolved to be a powerful approach to perform genome-wide or targeted reverse genetic screens to identify genes involved in various cellular pathways ( Sharma and Rao 2009 ; Mohr 2014 ; Chen and Xu 2016 ; Agrawal and Hardin 2016 ; Vissers et al 2016 ). For instance, such screens have identified novel genes involved in Drosophila nervous system development ( Koizumi et al 2007 ) and wound closure ( Lesch et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…We also noticed PP1-96a knockdown showed weak circadian defects: One dsRNA line (BL40906) exhibited slightly lengthened period in tim-GAL4 and Pdf-GAL4 ; the other non-overlapping line (BL42641) only exhibited reduced rhythmicity in tim-GAL4 , not in Pdf-GAL4 . A recent study also found that PP1-96a knockdown lengthened circadian period in tim-GAL4 and Pdf-GAL4 [60]. Although we cannot exclude SUR-8 might also affect PER through PP1-96A since PP1-87B and PP1-96A are in a complex, PP1-87B is likely the main subunit that interacts with SUR-8.…”
Section: Discussionmentioning
confidence: 72%